Damage Control Surgery for Hepatocellular Cancer Rupture in an Elderly Patient: Survival and Quality of Life. (4th October 2015) - Bouliaris, Konstantinos; Christodoulidis, Grigorios; Symeonidis, Dimitrios; Diamantis, Alexandros; Tepetes, Konstantinos
Abstract : Spontaneous rupture of hepatocellular carcinoma (HCC) is a rare emergency condition with high mortality rate. Successful management depends on patients' hemodynamic condition upon presentation and comorbidities, correct diagnosis, HCC status, liver function, and future liver remnant, as well as available sources. There is still a debate in the literature concerning the best approach in this devastating complication. Nevertheless, the primary goal should be a definitive bleeding arrest. In most cases, patients with spontaneous rupture of HCC present with hemodynamic instability, due to hemoperitoneum, necessitating an emergency treatment modality. In such cases, transcatheter arterial embolization (TAE) should be the treatment of choice. Emergency liver resection is an option when TAE fails or in cases with preserved liver function and limited tumors. Otherwise, damage control strategies, as in liver trauma, are a reasonable alternative. We report a case of an elderly patient with hemoperitoneum and hypovolemic shock from spontaneous rupture of undiagnosed HCC, who was treated successfully by emergency surgery and damage control approach.